Telaah Historis Perkembangan Orientalisme Abad XVI-XX - Rendra Khaldun (Universitas Islam Negeri Mataram, 2007)
Studies on relationship between West and Islam are still important to do till the recent times. The two cultures have been interacting one another for long time and will always do so in the future. To some Muslims point of view, West (Christianity) and East (Islam) become “eternal enemy” to each other. It can be traced in many biased view of orientalist about Islam and Muslims’ hatred against them. In this article I explore background of Islamic studies taken by orientalists. At first, orientalists transformed knowledge from Islam world to West through translating Muslim works into Western languages. As effect of Crusade 1, some orientalists do Islamic studies in order to criticize and weaken Islam through their misinterpretation and negative description about Islam. The come of Enlightenment turned some orientalits’ views on Islam into more neutral and likeable to Muslim. Their motivation to study Islam is only for the sake of knowledge development. Studies on relationship between West and Islam are still important to do till the recent times. The two cultures have been interacting one another for long time and will always do so in the future. To some Muslims point of view, West (Christianity) and East (Islam) become “eternal enemy” to each other. It can be traced in many biased view of orientalist about Islam and Muslims’ hatred against them. In this article I explore background of Islamic studies taken by orientalists. At first, orientalists transformed knowledge from Islam world to West through translating Muslim works into Western languages. As effect of Crusade 1, some orientalists do Islamic studies in order to criticize and weaken Islam through their misinterpretation and negative description about Islam. The come of Enlightenment turned some orientalits’ views on Islam into more neutral and likeable to Muslim. Their motivation to study Islam is only for the sake of knowledge development.